Implicações da formação do PNAIC nas compreensões dos professores sobre as elaborações de conceitos matemáticos pelas crianças do ciclo de alfabetização - Giombelli, Cirlei (2016)
This work aimed to determine whether and in what sense the formation of PNAIC helped teachers understand how mathematical concepts are designed by the children of the elementary school literacy cycle. The focus was restricted to the study of the conceptual field of additive structures. The research is based on the authors of Historical-Cultural Psychology, Mathematics Education and Psychology of Mathematics Education (Vergnaud and Duval) that assist in understanding and understanding of the development of mathematical concepts. In this research, 32 teachers participated in the literacy cycle (half of them attended the training course PNAIC - numeracy 2014) all effective at Public Concordia-SC. As data collection instruments, we used a questionnaire to profile the survey participants and a tool designed specifically for research, compound problems of additive structures, processing, composition and comparison, which had been settled by some of the children in classroom. The instrument was applied in dyads to investigate the proposed objective. It was observed that the teachers still have little clarity about the different types of problems and although almost all already take into account the different forms of representation and different strategies used by children, the vast majority still have difficulty in inferring the cognitive processes underlying these strategies. Thus, there is still a significant weakness in the knowledge of teachers, related to additive structures, having been found differences between the teachers who participated and those who did not participate in PNAIC. On the other hand, the analysis of policy proposals showed that the group who participated in the PNAIC reveals greater awareness of the need for intervention before possible errors; greatest concern to hear the child's views and regular interventions from them, greater understanding of the problems involve understanding of mathematical relationships and can not be reduced only to language issues and greater recognition of the need and the importance of using different ways representation. Thus, the results suggest that the formation of PNAIC is causing some changes in teaching practices that, for now, do not reflect conceptual changes relating to the content taught, at least with regard to the field of additive structures.